A modular multilevel converter type solid state transformer with internal model control method. (February 2017) - Li, Yong; Han, Jiye; Cao, Yijia; Li, Yunxuan; Xiong, Jiamin; Sidorov, Denis; Panasetsky, Daniil
Highlights: A modular multilevel type solid state transformer (MMC-SST) topology and its corresponding internal model control (IMC) method is proposed and a dual-loop control structure is developed. The MMC-SST with IMC has the strong ability to resist load disturbance, and can enhance the robustness of system. Abstract: To overcome the limitation of the existing topologies and control strategies of SST, a modular multilevel converter type solid state transformer (MMC-SST) with internal model control method is proposed in this paper. First, the structure and operating characteristics of MMC-SST are analyzed, and accordingly its mathematical model of input- and output-stage under synchronous rotating coordinate is established. Secondly, a new kind of dual-loop control structure combine with the internal model control (IMC) current inner loop and proportional integral (PI) voltage outer loop is developed, according to the characteristics of IMC. Lastly, a simulation model is established and the typical operating cases, i.e., the grid side voltage variation, load change, grid and load side power factor deviation, are simulated. Results show that the internal model control based MMC-SST can run stable under the required power factor, and the good performances such as fast voltage and current response speed, strong anti-disturb ability to load, and enhanced robustness on system operation are demonstrated.